2019
DOI: 10.1101/561472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human loss-of-function variants suggest that partial LRRK2 inhibition is a safe therapeutic strategy for Parkinson’s disease

Abstract: Human genetic variants predicted to cause loss-of-function of protein-coding genes (pLoF variants) provide natural in vivo models of human gene inactivation, and can be valuable indicators of gene function and the potential toxicity of therapeutic inhibitors targeting these genes 1,2 . Gain-of-kinase-function variants in LRRK2 are known to significantly increase the risk of Parkinson's disease 3,4 , suggesting that inhibition of LRRK2 kinase activity is a promising therapeutic strategy. While preclinical studi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…However, the lack of a robust brain phenotype precludes us from answering the question of the directional relationship between LRRK2 and RAB29 with the data presented here. There are peripheral phenotypes in models of LRRK2 deficiency, such as accumulation of lysosomal markers in the kidney and invasion of the alveolar space by type-II pneumocytes in the lung (Baptista et al, 2013;Kuwahara et al, 2016;Whiffin et al, 2019). Further studies on the peripheral phenotypes in the Rab29 -/and Lrrk2 -/-/Rab29 -/animals will be required to clarify whether LRRK2 is upstream or downstream of RAB29 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a robust brain phenotype precludes us from answering the question of the directional relationship between LRRK2 and RAB29 with the data presented here. There are peripheral phenotypes in models of LRRK2 deficiency, such as accumulation of lysosomal markers in the kidney and invasion of the alveolar space by type-II pneumocytes in the lung (Baptista et al, 2013;Kuwahara et al, 2016;Whiffin et al, 2019). Further studies on the peripheral phenotypes in the Rab29 -/and Lrrk2 -/-/Rab29 -/animals will be required to clarify whether LRRK2 is upstream or downstream of RAB29 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…10 The underlying pathogenic mechanism of LRRK2-linked PD is currently unknown, but a great deal of focus has been placed on the ability of the p.G2019S mutation to increase LRRK2 kinase activity, especially since loss-of-function mutations do not seem to be contributing to disease. 11,12 In the last several years, genome-wide association studies (GWAS) have identified an everincreasing number of risk loci for PD. Individually, each of these loci confers modest effects on risk for disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, other reports have not replicated this finding and instead nominated variants in SNCA as modifiers of LRRK2 mutation penetrance . The underlying pathogenic mechanism of LRRK2‐ linked PD is currently unknown, but a great deal of focus has been placed on the ability of the p.G2019S mutation to increase LRRK2 kinase activity, especially given that loss‐of‐function mutations do not seem to be contributing to disease …”
mentioning
confidence: 99%